Photoinduced topological transformation of cyclized polylactides for switching the properties of homocrystals and stereocomplexes1. Issue 19 (21st May 2015) - Sugai, Naoto; Asai, Shigeo; Tezuka, Yasuyuki; Yamamoto, Takuya
<x xml:space="preserve">Abstract</x> A new methodology for a stimuli-responsive polymer was proposed on the basis of cyclization and photocleavage. This requires only a single reaction per polymer molecule.